Can Biliary Papillomatosis Recur after Liver Transplantation in the Absence of Infiltrative Carcinoma?. (July 2018) - Maestro, Oscar Caso; Muñoz, Carlos; Alonso, Iago Jusot; Pérez-Flecha, Marina; Municio, Alejandro Manrique; Quinto, Alberto Marcacuzco; Alonso, Laura; Pulido, Jorge Calvo; Del Pozzo Elso, Pilar; Pulido, Felix Cambra; Sesma, Alvaro Garcia; Romero, Carlos Jiménez
Abstract : Introduction: Biliary papillomatosis (BP) is a rare entity characterized by the presence of multiple papillary tumours in the intrahepatic and/or extrahepatic biliary tree. Chappet was the first who described in 1894 this condition and less than 100 cases have been described in the literature since then. To our knowledge, only 8 cases of BP treated with LT have been described in the literature in the since the year 2000. Vibert et al 6 argued in 2010 that in the absence of infiltrative carcinoma and positive lymph nodes, LT is the best choice of treatment and that LT might even be considered in highly selected patients with superficial foci of malignancy without positive lymph nodes. Material and Methods: We report the case of a 43-year-old male who was admitted to our hospital with cholangitis. Complementary studies revealed a wide dilatation of the biliary tree and a tumour over the papilla. He underwent cephalic pancreaticoduodenectomy and the histological study showed the presence of BP affecting the margins of biliary and pancreatic resections. Total pancreatectomy was carried out to exclude carcinoma foci in the pancreas and finally LT was performed. No carcinoma foci or lymph node infiltration were identified in the histological study. After 24 months the patient developed a large hepatic recurrence and died a few weeks after the diagnosis. Discussion: BP is considered a premalignant disease with a high risk of malignant transformation. Surgical treatment must be aggressive to achieve resection of all affected areas. Since 2000, only 8 cases of diffuse BP treated with LT have been described in the literature. All of them had both intra- and extrahepatic biliary tract involvement and in 3 cases the main pancreatic duct was affected too. Of the 8 cases described, only 4 histological studies showed invasive carcinoma in the explant liver after transplantation, in 1 of them with lymph node involvement. Two of them had recurrence at 16 months and at 6 years respectively, and the remaining 2 were alive without recurrence at 18 and 22 months, respectively. The present case is the first to describe recurrence of the disease after LT in the absence of invasive carcinoma and positive lymph nodes, confirming the recurrent nature of the disease despite a radical curative treatment. Prognosis in cases of recurrence is bad regardless of the presence of foci of invasive carcinoma in the surgical specimen, since all published cases with recurrence after LT died in a short period of time. Probably, immunosuppression makes the recurrence of the disease more aggressive and with a worse prognosis. Conclusion: BP is a premalignant disease that can recur after liver transplantation even in the absence of infiltrative carcinoma foci.